1984
DOI: 10.1083/jcb.98.3.934
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of actin and tubulin distribution to bud growth in wild-type and morphogenetic-mutant Saccharomyces cerevisiae.

Abstract: The distribution of actin in wild-type cells and in morphogenetic mutants of the budding yeast Saccharomyces cerevisiae was explored by staining cells with fluorochromelabeled phallotoxins after fixing and permeabilizing the cells by several methods . The actin appeared to be localized in a set of cortical spots or patches, as well as in a network of cytoplasmic fibers . Bundles of filaments that may possibly correspond to the fibers visualized by fluorescence were observed with the electron microscope.The put… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
745
2

Year Published

1996
1996
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 819 publications
(771 citation statements)
references
References 76 publications
24
745
2
Order By: Relevance
“…The mutant cells produced grossly elongated buds (Figure 5, D and F) in which the nuclear cycle continued ( Figure 5G). This phenotype is very similar to that associated with a complete loss of septin function (Hartwell, 1971;Adams and Pringle, 1984;Longtine et al, 1996), and Figure 1. Suppression of the growth, morphological, and septinorganization defects of a cdc12-6 mutant by multicopy BEM3, RGA1, or RGA2.…”
Section: Defective Septin Organization In Cdc42p Gap Mutantssupporting
confidence: 48%
See 3 more Smart Citations
“…The mutant cells produced grossly elongated buds (Figure 5, D and F) in which the nuclear cycle continued ( Figure 5G). This phenotype is very similar to that associated with a complete loss of septin function (Hartwell, 1971;Adams and Pringle, 1984;Longtine et al, 1996), and Figure 1. Suppression of the growth, morphological, and septinorganization defects of a cdc12-6 mutant by multicopy BEM3, RGA1, or RGA2.…”
Section: Defective Septin Organization In Cdc42p Gap Mutantssupporting
confidence: 48%
“…It has long been known that septin mutants produce hyperpolarized, abnormally elongated buds (Hartwell, 1971;Adams and Pringle, 1984). Recent observations have suggested that at least part of the reason for this is that septin mutants have a transient, Swe1p-dependent delay in the G2-M transition, which results in a delay in the switch from polarized to isotropic growth of the bud (Carroll et al, 1998;Barral et al, 1999;Shulewitz et al, 1999;Longtine et al, 2000).…”
Section: Role Of the Septins In Bud Morphogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…The myosins move along cables of actin filaments that radiate throughout the cell in arrays oriented toward growth sites (Adams and Pringle, 1984;Kilmartin and Adams, 1984).…”
Section: Introductionmentioning
confidence: 99%